Ivermectin systemic availability in adult volunteers treated with different oral pharmaceutical formulations - Ceballos, Laura (2023)
Ivermectin (IVM) is currently approved as an antiparasitic agent for human use in the treatment of onchocerciasis, lymphatic filariasis, strongyloidiasis, scabies, and pediculosis. Recent findings indicate that IVM may reach other pharmacological targets, which accounts for its proven anti-inflammatory/immunomodulatory, cytostatic, and antiviral effects. However, little is known about the assessment of alternative drug formulations for human use. Objective: To compare the systemic availability and disposition kinetics of IVM orally administered as different pharmaceutical formulations (tablet, solution, or capsule) to healthy adults. Experimental design/main findings: Volunteers were randomly assigned to 1 of 3 experimental groups and orally treated with IVM as either, a tablet, solution, or capsules at 0.4 mg/kg in a three-phase crossover design. Blood samples were taken as dried blood spots (DBS) between 2 and 48 h post-treatment and IVM was analyzed by HPLC with fluorescence detection. IVM Cmax value was higher (P < 0.05) after the administration of the oral solution compared to treatments with both solid preparations. The oral solution resulted in a significantly higher IVM systemic exposure (AUC: 1653 ng h/mL) compared to the tablet (1056 ng h/mL) and capsule (996 ng h/mL) formulations. The simulation of a 5-day repeated administration for each formulation did not show a significant systemic accumulation. Conclusion: Beneficial effects against systemically located parasitic infections as well as in any other potential therapeutic field of IVM application would be expected from its use in the form of oral solution. This pharmacokinetic-based therapeutic advantage without the risk of excessive accumulation needs to be corroborated in clinical trials specifically designed for each purpose.